Global polity e policies: verso forme nuove di conoscenza del potere (Glocalism: Journal of Culture, Politics and Innovation, 2015)
Global polity and policies are a forceful new factor in the changing face of power, both how it is exercised and legitimatized. The perceptions of politics in the traditional and more widespread social representations can also change by power being modified. For these reasons the article focuses chiefly on the relationship between knowledge of power and global politics. The knowledge of how power comes about and is dealt out in the global system is often still conditioned by models, theories and paradigms linked to the ways in which the State organizes power today. After the breakdown of the jus publicum europaeum and sovereignty, knowledge of power and politics today is paramount to explain the new type of political, burocratic power exercised by international institutions and regimes, equal or unequal alliances between political classes, international and domestic oligarchies, the way in which information technology constantly changes the traditional representations of politics and its very pervasiveness. The article’s concluding thesis is that it is above all the new or not so new approaches characterizing global politics and policies which will prove indispensible for us to adequately get to grips with and suitably systemize the ways in which power currently comes about and is dealt out.
Keywords: knowledge of politics; oligarchies; information technology; jus publicum europaeum; sovereignty